Influence of Limited Mouth Opening on Guided Endodontic Access and Its Clinical Management: A Case Report - Moreira Júnior, Gil; Moreira Maia, Lucas; Morais Barbosa, Camila de Freitas; de Toubes, Kênia Maria Pereira Soares; Machado, Vinícius de Carvalho; Tavares, Warley Luciano Fonseca; Ribeiro Sobrinho, Antônio Paulino (Iranian Endodontic Journal, 2025)
This case report presents the innovative application of ultrasonic points combined with a graphite-marked endodontic guide in a case of restricted vertical space. A 71-year-old female patient with root canal obliteration in the second left mandibular molar was referred for treatment. The patient was experiencing spontaneous pain. Using data from cone-beam computed tomography and surface scans, a virtual 3D guide was developed and positioned. As the patient presented limited interocclusal space, black graphite was inserted through the drill path to mark the pathway. The guide was withdrawn, shorter ultrasonic points were inserted 2 mm into the marked dentin, and this process was repeated until the root canals were localized. The root canals were subsequently shaped and filled. The guide drill path effectively served as a reference for ultrasonic points, enabling successful localization of the root canals. Graphite-marked guide path facilitated access to obliterated root canals in the presence of limited interocclusal space.